A pilot randomised controlled trial of modafinil during acute methamphetamine withdrawal: Feasibility, tolerability and clinical outcomes. (27th May 2012) - Lee, Nicole; Pennay, Amy; Hester, Robert; McKetin, Rebecca; Nielsen, Suzi; Ferris, Jason
Abstract Introduction and Aims There are no medications approved for the treatment of methamphetamine withdrawal. Wake‐promoting agent modafinil has recently been proposed as a viable option. This paper reports on the results of a pilot study that tested the feasibility of modafinil in an inpatient withdrawal setting during acute methamphetamine withdrawal. Design and Methods In a double‐blind, randomised, placebo‐controlled study, 19 methamphetamine dependent participants received modafinil (n = 9) or placebo (n = 10) daily for 7 days (200 mg for the first 5 days and 100 mg on days 6 and 7). Primary outcomes were retention in treatment and severity of withdrawal symptoms. Secondary outcomes were methamphetamine craving, sleep and physiological outcomes. Results There were no significant differences between groups on retention in treatment, withdrawal severity, craving, sleep or physiological outcomes. There were no adverse events or side‐effects reported. Conclusions Modafinil was found to be tolerable and well accepted by methamphetamine users and feasible for short‐term inpatient withdrawal, but the sample was too small to detect treatment effects. Larger trials are needed to establish efficacy.